2013
DOI: 10.1186/1472-6963-13-303
|View full text |Cite
|
Sign up to set email alerts
|

Into the abyss: diabetes process of care indicators and outcomes of defaulters from a Canadian tertiary care multidisciplinary diabetes clinic

Abstract: BackgroundContinuity of care is essential for good quality diabetes management. We recently found that 46% of patients defaulted from care (had no contact with the clinic for 18 months after a follow-up appointment was ordered) in a Canadian multidisciplinary tertiary care diabetes clinic. The primary aim was to compare characteristics, diabetes processes of care, and outcomes from referral to within 1 year after leaving clinic or to the end of the follow-up period among those patients who defaulted, were disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 26 publications
(30 reference statements)
0
20
1
Order By: Relevance
“…A total of 32 patient factors from 19 studies (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34) were identified (Table II). The studies investigated the different patient factors that may affect an individual's willingness and ability to return for followup at their respective health clinics.…”
Section: Patient Factorsmentioning
confidence: 99%
See 3 more Smart Citations
“…A total of 32 patient factors from 19 studies (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34) were identified (Table II). The studies investigated the different patient factors that may affect an individual's willingness and ability to return for followup at their respective health clinics.…”
Section: Patient Factorsmentioning
confidence: 99%
“…(18,30) For alcohol, smoking and substance use, several studies showed no association with FUNA. (19,27,29,30,33) However, three studies found that FUNA was positively associated with smoking. (18,19,23) As for knowledge, beliefs and attitudes, patients with FUNA were positively associated with poor knowledge of their disease, belief that their medications do not work and lack of satisfaction with their DM care.…”
Section: Patient Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…10,12 The clinical outcomes from care that patients with T2D received at SQUH did not match those from Europe, 17,18 North America, 19 Canada, 20 and Australia. 21 Compared to reports from similar tertiary centers in Europe, 17 Canada, 20 and Australia, 21 clinical outcomes in Omani patients were lower. For example, 42% of the patients in Portugal, USA, and Canada were at HbA 1C goal (<7.0%) 17,19 compared to 22% in Oman.…”
Section: Discussionmentioning
confidence: 54%